Immunosenescence of Natural Killer Cells, Inflammation, and Alzheimer's Disease. (1st November 2018) - Solana, Corona; Tarazona, Raquel; Solana, Rafael
Abstract : Alzheimer's disease (AD) represents the most common cause of dementia in the elderly. AD is a neurodegenerative disorder characterized by progressive memory loss and cognitive decline. Although the aetiology of AD is not clear, both environmental factors and heritable predisposition may contribute to disease occurrence. In addition, inflammation and immune system alterations have been linked to AD. The prevailing hypothesis as cause of AD is the deposition in the brain of amyloid beta peptides (A β ). Although A β have a role in defending the brain against infections, their accumulation promotes an inflammatory response mediated by microglia and astrocytes. The production of proinflammatory cytokines and other inflammatory mediators such as prostaglandins and complement factors favours the recruitment of peripheral immune cells further promoting neuroinflammation. Age-related inflammation and chronic infection with herpes virus such as cytomegalovirus may also contribute to inflammation in AD patients. Natural killer (NK) cells are innate lymphoid cells involved in host defence against viral infections and tumours. Once activated NK cells secrete cytokines such as IFN- γ and TNF- α and chemokines and exert cytotoxic activity against target cells. In the elderly, changes in NK cell compartment have been described which may contribute to the lower capacity of elderly individuals to respond to pathogens and tumours. Recently, the role of NK cells in the immunopathogenesis of AD is discussed. Although in AD patients the frequency of NK cells is not affected, a high NK cell response to cytokines has been described together with NK cell dysregulation of signalling pathways which is in part involved in this altered behaviour.